Measurement of Total Plasma Homocysteine, Folic Acid, Vitamin B12 and Vitamin D3 Levels among Osteoporotic Women in Duhok City (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
Background and objectives: Recent studies suggest that high homocysteine levels are associated with an increased risk of fractures. Homocysteine levels are known to be influenced by vitamin B12, vitamin D3 and folic acid status. Elevated plasma total homocysteine (tHcy) and deficiencies of folate and vitamin B12 are associated with risk of osteoporosis and bone loss. Therefore, this study aims to examine whether high plasma levels of homocysteine and low plasma levels of folate, vitamin B12 and vitamin D3 predicted a bad prognosis of bone health or not.Methods: A cross sectional study was conducted on (90) women whose ages were between (45–85 years old) in 2017–2018. Recorded information on T – score values were obtained from computerized DEXA machine at the Duhok Rheumatic disease and Rehabilitation center. Independent t – test by (SPSS version 23) program was used to estimate relationship and risk assessment among study parameters comparing to levels of plasma total homocysteine (tHcy).Results: Hyperhomocysteinemia is associated with skeletal abnormalities and osteoporosis. We tested whether levels of homocysteine and critical co-enzymes of homocysteine metabolism, such as vitamin B12, D3 and folate which are related to bone mineral density (BMD) measured by DEXA. The current data demonstrates that homocysteine is highly significant (P value < 0.01) with each of age, waist circumferences (C. W.), vitamin B12, folic acid, vitamin D3 and T- score quartiles, also significant (P value < 0.05) with Body Mass Index (BMI), calcium (Ca+) and Total Body Fat percent (TBF %).Conclusions: Homocysteine seems to be a predictor for development of osteoporosis among study population (elderly menopaused women in Duhok city). The present data suggest a major association between folate, vitamin B12, vitamin D3 and bone mineralization. Our data documented the hypothesis that homocysteine may play a role in the pathogenesis of osteoporotic fractures.